EVALUASI STRATEGI MANAJEMEN DALAM MENGENDALIKAN KINERJA KEUANGAN PT. VALE INDONESIA, TBK - Raden Ayu Silvia Riani; Haris Maupa; Abdullah Sanusi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
In 2016, when nickel prices were in a low position throughout history, PT Vale not only managed to achieve strong performance but also succeeded in laying a solid foundation for sustainable growth in the future. This study aims to evaluate management strategies in controlling financial performance that occurred at PT. Vale Indonesia, Tbk and to provide enlightenment and suggestions as an evaluation material for companies in taking more measurable, more effective and efficient strategic measures to be more sustainable and remain competitive. This research is based on qualitative approach. The theoretical framework is obtained through articles, literature and case studies relevant to the research. Empirical information is gained through experience experienced by the researcher, interaction, formal and non-formal communication, and observation. The results of this study indicate that the evaluation and testing of PT Vale strategy using SWOT analysis and TOWS matrix has been done correctly with the proven that internal factors in PT Vale have a very strong influence on the decisions and strategic steps taken by the company. In this study, evaluation of strategic decisions determined by firms is evaluated through QSPM analysis. The evaluation conducted at PT Vale proves that QSPM can be a very precise strategic planning tool.